Variation in the Composition and Pore Function of Major Outer Membrane Pore Protein P2 of Haemophilus influenzae from Cystic Fibrosis Patients - Regelink, Annette G. (American Society for Microbiology, 1999)
We investigated the relationship between susceptibility to β-lactam antibiotics and variation in the major outer membrane protein P2 (OmpP2; also called porin) of persistent nonencapsulated Haemophilus influenzae isolated from cystic fibrosis patients. Nine OmpP2 variants were selected from two distinct H. influenzae strains from two patients extensively treated with β-lactam antibiotics. The variants differed in their susceptibilities to at least two β-lactam antibiotics. By detergent extraction and column chromatography, OmpP2 was purified from two variants that were derived from strain 70 and that differed notably in their susceptibilities to β-lactam antibiotics. The proteins were reconstituted into black lipid membranes for measurement of porin function. OmpP2 from the more resistant isolate (isolate 70b) had a smaller channel conductance than OmpP2 of the more susceptible isolate (isolate 70f). DNA sequencing of ompP2 of these isolates revealed single nonsynonymous base differences; there were changes in the amino acid sequence corresponding to surface-exposed loops 4, 5, 6, and 8. Changes in loops 4, 5, and 6 were previously shown to result in antigenic differences. Beside these mutations, variants of strain 70 showed additional mutations in loop 1 and nonexposed loop 3. Taken together, our results suggest that in variants of strain 70, nonsynonymous point mutations accumulated both in the sequences of ompP2 coding for antigen-variable loops and in other loops, notably, loops 1 and 3. The latter changes are suggested to affect the permeability of the porin channel.